Central cortical cleanup and zonular deficiency - Mansour AM (Dove Medical Press, 2016)
Ahmad M Mansour,1,2 Rafic S Antonios,1 Iqbal Ike K Ahmed3 1Department of Ophthalmology, American University of Beirut, Beirut, Lebanon; 2Department of Ophthalmology, Rafic Hariri University Hospital, Beirut, Lebanon; 3Department of Ophthalmology, University of Toronto, Toronto, ON, Canada Background: Complete removal of the cortex has been advocated to prevent posterior capsular opacification but carries the risk of zonular dehiscence, hence there is a need for a safe maximal cortical cleanup technique in eyes with severe diffuse zonulopathy in subjects above age 90. Methods: We used bimanual central cortical cleaning by elevating central fibers and aspirating them toward the periphery. Peripheral cortical fibers were removed passively only when they became loose due to copious irrigation. A one-piece foldable implant was inserted without a capsular tension ring. Postoperative corticosteroid drops were used. Results: This technique was safely performed in a dozen eyes with severe pseudo-exfoliation or brunescent cataract with weak zonules. Posterior capsular rupture, iritis, vitreous loss, and lens subluxation were not observed. Moderate capsular phimosis occurred but with maintained central vision. Conclusion: The dogma of “complete cortical cleanup” in severe zonulopathy needs to be revisited in favor of a clear visual axis with maximal preservation of the damaged zonules. This technique is ideal in patients above age 90 where posterior capsular opacification and late dislocation of intraocular lens–capsule bag complex are unlikely to occur until several years postoperatively. Keywords: brunescent cataract, cortex aspiration, phacoemulsification, pseudo-exfoliation, weak zonules